WEIGHT STATUS, PHYSICAL FITNESS AND SATISFACTION WITH LIFE AMONG ELEMENTARY SCHOOL CHILDREN. A PILOT STUDY - Rosa Guillamón, Andrés (2016)
Physical fitness is a biomarker of overall health as well as a powerful predictor of longevity and quality of life since childhood. The purpose of this study is to analyze the relationship between weight status, physical fitness, and satisfaction with life in elementary school children. A cross-sectional descriptive study was conducted including 214 school children (120 females and 94 males), ages 8 to11. Weight and height were measured, and body mass index (BMI) was calculated. Muscle strength, speed and agility displacement, and aerobic capacity were evaluated using the ALPHA-Fitness Battery. Students were categorized by physical fitness level (low, medium and high) and weight status (normal-weight, overweight and obesity). Life satisfaction was measured by the Satisfaction with Life Scale. Statistical analyzes indicate that obese school children have lower values in the Satisfaction with Life Scale. In addition, school children with medium-high levels of fitness have higher records in the life satisfaction scale. Results suggest that weight status and physical fitness could be determining factors in the perception of life satisfaction in 8 to 11 year-old school children.